Radiation Injury Treatment Network®: Preparedness Through a Coalition of Cancer Centers. Issue 2 (August 2016) - Case, Cullen
Abstract : Abstract: This article provides an overview of Radiation Injury Treatment Network® (RITN), its preparedness activities and capabilities, including training and educating over 11, 500 hospital staff, coordinating over 500 exercises, developing treatment guidelines, developing standard operating procedures, and being recognized by the U.S. federal government as a national response asset. The RITN provides comprehensive evaluation and treatment for victims with marrow toxic injuries. Many of the casualties from the detonation of an improvised nuclear device (IND) (a.k.a. terrorist nuclear bomb) with only radiation injuries will be salvageable; however, they would require outpatient and/or inpatient care. Recognizing this, the U.S. National Marrow Donor Program (NMDP), U.S. Navy, and American Society for Blood and Marrow Transplantation (ASBMT) collaboratively developed RITN, which comprises medical centers with expertise in the management of bone marrow failure. The medical community will undoubtedly be taxed by the resulting medical surge from an IND despite the well-defined United States emergency medical system, the National Disaster Medical System; however, one area that is unique for radiological disasters is the care for casualties with acute radiation syndrome. Hematologists and oncologists purposefully expose their cancer patients to high doses of radiation and toxic chemicals for chemotherapy as they treat their patients, resulting in symptoms not unlike casualties with exposure to ionizing radiation from a radiological disaster. This makes the staff from cancer centers ideal for the specialized care that will be required for thousands of casualties following a mass casualty radiological incident. The RITN is a model for how a collaborative effort can fill a readiness gap—through its network of 76 hospitals, blood donor centers, and cord blood banks, the RITN is preparing to provide outpatient care and specialized supportive care to up to 63, 000 radiological casualties.